Improving Brain Metastases Outcomes Through Therapeutic Synergy Between Stereotactic Radiosurgery and Targeted Cancer Therapies - Rubino, Sebastian; Oliver, Daniel E.; Tran, Nam D.; Vogelbaum, Michael A.; Forsyth, Peter A.; Yu, Hsiang-Hsuan Michael; Ahmed, Kamran; Etame, Arnold B. (Frontiers in Oncology, 2022)
Brain metastases are the most common form of brain cancer. Increasing knowledge of primary tumor biology, actionable molecular targets and continued improvements in systemic and radiotherapy regimens have helped improve survival but necessitate multidisciplinary collaboration between neurosurgical, medical and radiation oncologists. In this review, we will discuss the advances of targeted therapies to date and discuss findings of studies investigating the synergy between these therapies and stereotactic radiosurgery for non-small cell lung cancer, breast cancer, melanoma, and renal cell carcinoma brain metastases.